Postmodern plagiarisms : cultural agenda and aesthetic strategies of appropriation in US-American literature (1970-2010) - Horn, Mirjam (Buchreihe der Anglia ;, 2015)
Postmodern Plagiarisms investigates literary plagiarism and how it serves as a strategic act in several postmodern US-American texts. The book discusses the strong link between author and text at the interface between economics, law, and literary theory, and the complex process of its subversive violation. As a consequence, literary plagiarism is seen as a cultural litmus test for the dynamic notions of authorship, originality, and creativity.